A spotlight on the interplay between Wnt/β-catenin signaling and circular RNAs in hepatocellular carcinoma progression - Mafi, Alireza; Rismanchi, Hamidreza; Malek Mohammadi, Mohaddese; Hedayati, Neda; Ghorbanhosseini, Seyedeh Sara; Hosseini, Seyed Ali; Gholinezhad, Yasaman; Mousavi Dehmordi, Rohollah; Ghezelbash, Behrooz; Zarepour, Fatemeh; Taghavi, Seyed Pouya; Asemi, Zatollah; et al. (Frontiers in Oncology, 2023)
Hepatocellular carcinoma (HCC) is one of the deadliest cancers due to multifocal development and distant metastasis resulting from late diagnosis. Consequently, new approaches to HCC diagnosis and treatment are required to reduce mortality rates. A large body of evidence suggests that non-coding RNAs (ncRNAs) are important in cancer initiation and progression. Cancer cells release many of these ncRNAs into the blood or urine, enabling their use as a diagnostic tool. CircRNAs are as a members of the ncRNAs that regulate cancer cell expansion, migration, metastasis, and chemoresistance through different mechanisms such as the Wnt/β-catenin Signaling pathway. The Wnt/β-catenin pathway plays prominent roles in several biological processes including organogenesis, stem cell regeneration, and cell survival. Aberrant signaling of both pathways mentioned above could affect the progression and metastasis of many cancers, including HCC. Based on several studies investigated in the current review, circRNAs have an effect on HCC formation and progression by sponging miRNAs and RNA-binding proteins (RBPs) and regulating the Wnt/β-catenin signaling pathway. Therefore, circRNAs/miRNAs or RBPs/Wnt/β-catenin signaling pathway could be considered promising prognostic and therapeutic targets in HCC.